2014
DOI: 10.1590/s1516-89132014000100008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low level laser therapy on injured skeletal muscle

Abstract: The main purpose of the present study was to investigate the effects of low-level laser therapy (LLLT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Both Roth et al and Weiss et al demonstrated that injured areas of muscle were filled with new myofibrils capable of contractile activity [28, 37]; additionally, Shefer et al showed that laser irradiation could stimulate the satellite cells near myofibrils and form new myofibrils for muscular repair [27]. Moreover, laser irradiation could modulate the collagen content in injured areas through nuclear factor kappa-B (NF-kB) gene expression, collagen I and III remodeling [38], and a reduction in collagen content in skeletal muscles [39]. Rodriguez et al indicated that the hADSCs could repair a posterior tibialis muscle injury via formation and fusion of new myotubes [40].…”
Section: Discussionmentioning
confidence: 99%
“…Both Roth et al and Weiss et al demonstrated that injured areas of muscle were filled with new myofibrils capable of contractile activity [28, 37]; additionally, Shefer et al showed that laser irradiation could stimulate the satellite cells near myofibrils and form new myofibrils for muscular repair [27]. Moreover, laser irradiation could modulate the collagen content in injured areas through nuclear factor kappa-B (NF-kB) gene expression, collagen I and III remodeling [38], and a reduction in collagen content in skeletal muscles [39]. Rodriguez et al indicated that the hADSCs could repair a posterior tibialis muscle injury via formation and fusion of new myotubes [40].…”
Section: Discussionmentioning
confidence: 99%
“…The laser does this by stimulating the satellite cells adjacent to the adult myofibrils [ 19 ]. In addition to increasing myofibrils, laser by modifying the Nuclear Factor Kappa B (NF-κB) expression causes collagen remodeling [ 36 ] and reduces collagen levels [ 37 ], thereby advancing the muscle repair process. In the present study, the amount of collagen in the laser group also confirms the laser's regulatory role on collagen during the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…LLLT is used to speed up the process of regeneration as noted by Renno et al 17 , who evaluated rats submitted to cryolesion and treated with AsGaAl laser (808 nm, 50 mw, and 10 J/cm 2 and 50 J/cm 2 energy densities) and found reduction in the areas of cellular infiltrate and injury compared to the control group after 13 days. A similar result was found after 21 days of cryolesion in the control and malnourished groups in this work.…”
Section: Discussionmentioning
confidence: 99%